Geocultural power and the digital Silk Roads. (October 2022) - Winter, Tim
Only a select group of countries have systematically surveyed and classified, written and exhibited the history, religion and culture of others. Today, through its Belt and Road Initiative, China begins to join this group. Proclamations to 'revive' the Silk Roads for the twenty-first century have triggered a profusion of cultural sector projects – led in part by the behemoths of China's technology industries, Tencent, Baidu and Huawei – as part of the Belt and Road Initiative cooperation and diplomacy architecture. This paper argues that geocultural power arises from having the capacity to write and map geocultural histories, and that digitalisation and the new cultural economies it creates is fast emerging as a powerful means for achieving this. It demonstrates how Big Earth Data, crowdsourced imagery and VR technologies afford geocultural thinking, and parallels are drawn with nineteenth-century Europe to consider such developments.